Teacher-Made YouTube Videos in Online EFL Classes: Non-English Department Students’ Perceptions and Practices - Atmojo, Arief Eko Priyo (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2022)
This research aims to seek answers on the students’ perceptions towards teacher-made YouTube videos for learning English online and how do they take advantage of the videos. Eight non-English department students were invited to become participants and they voluntarily accepted the invitation. Data were garnered through written reflections. It was then continued by three rounds of semi-structured focus group discussion. Coding was performed to analyze the data and done thrice at different times to ensure the credibility of the results. The results indicate the students’ general and detailed perceptions on the use of teacher-made YouTube videos which are very fruitful. The findings also show how the students use and take advantage of the videos and some difficulties they encounter. It implies that the student's perceptions and how they use and take advantage of the videos should be considered by EFL video creators in the future, including EFL teachers. Future researches may apply different methods, contexts, and participants.